Motto Hen Tecahi Yo Onomi T’mar Ni Hanased: Contextualization Religious Moderation in Port Numbay (Jayapura City) - Jakiyudin, Ahmad Havid (POROS ONIM: Jurnal Sosial Keagamaan, 2023)
Hen Tecahi Yo Onomi T'mar Ni Hanased is a motto that describes Port Numbay (Jayapura City). The contextualization of the motto is not only a symbol of writing, but also has implications for the values of religious moderation in Jayapura City. The purpose of this study is to provide an analysis of the implications of the contextualization of the Jayapura city motto on the values of religious moderation. The qualitative content analysis method is used as an approach in this study. The results showed that the motto Hen Tecahi Yo Onomi T'mar Ni Hanased is a form of representation of local wisdom of Port Numbay.  The motto has been attached to the community in Jayapura City, even textually the motto is written in many office agencies, government agencies, road balio, and school agencies. The contextualization of the motto contains religious moderation values that describe the life of the people of Jayapura City. The values of religious moderation reflected in the motto are the values of tolerance, unity, accommodating local culture, and creating religious harmony. Given that Jayapura City is known as a multi-ethnic area. So that the strengthening of the contextualization of the motto makes Port Numbay a peaceful city.